Pengaruh Profibilitas, Solvabilitas, Aktivitas Terhadap Nilai Perusahaan Minyak, Gas, Batubara - Agustinus Dandy Septyawan Surya Putra (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
This study investigates the influence of profitability, solvency, and activity financial ratios on firm value within the energy sector (oil, gas, and coal) listed on the Indonesia Stock Exchange from 2021 to 2023. Utilizing multiple linear regression analysis, the research demonstrates that profitability (ROA), solvency (DER), and activity (TATO) collectively and individually impact firm value (PBV). The findings suggest that financial performance management is crucial for enhancing firm value in this sector, especially in response to market dynamics and regulatory changes.